Printmaking terminology in cupcake mould to product artwork / Mursyidah Zainal Abidin , Mohd Razif Mohd Rathi and Wan Samiati Andriana Wan Mohd Daud - Zainal Abidin, Mursyidah; Mohd Rathi, Mohd Razif; Wan Mohd Daud, Wan Samiati Andriana (Research Management Institute (RMI), 2012)
Printmaking which always shows the conversational definition, meaning and practices as the remaking more then one production. Through varieties of media, it has develops to create multiple images. It related with things that have block as mark or images of surface.The aim of this research is to produce artwork based from the possible interpretation of printmaking definition and hopefully it can move away from flat two-dimensional prints to three-dimensional prints. The images produced by using cupcake mould in food industry as block to convey the idea as dynamic medium in visual art where printmaking can be described by three-dimensional visual language, medium and also techniques.The method of this study will encompass an observation focuses on the development of printmaking in Malaysia which the term has adopted and practice by printmakers. By understanding the meaning, the printmaking terminology will provide alternative way to develop, explores, search and learn another means of expression in making the artwork. As a printmaker, to create an artwork as a language for communication, will be widely understood and at the same time does not sacrifice artistic merits of printmaking as a medium truly unique, in creating new experience and possibilities.